2018
DOI: 10.1016/j.ebiom.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A New Metastatic Lymph Node Classification-based Survival Predicting Model in Patients With Small Bowel Adenocarcinoma: A Derivation and Validation Study

Abstract: BackgroundCurrent methods of lymph node (LN) staging are controversial in predicting the survival of SBA. We aimed to develop an alternative LN-classification-based nomogram to individualize SBA prognosis.MethodsBased on the data from the Surveillance, Epidemiology, and End Results (SEER) database of patients diagnosed with SBA between 2004 and 2014, we identified the cut-off points for the number of LNs examined and the number found to be metastatic using the K-adaptive partitioning (KAPS) algorithm. Using me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…indicators than the C-index, and the NRI indicated that the proposed nomogram reclassified the risk probabilities better than did the AJCC staging system, while the IDI demonstrated the superior ability of the constructed nomogram to distinguish cases compared with the AJCC staging system. Numerous previous studies have found benefits of applying DCA (29)(30)(31)(32)(33), and the results of the current study indicate that the 3-, 5-, and 10-year DCA curves yielded net benefits greater than those of the AJCC staging system, both in the training and validation sets (Figure 4).…”
Section: Discussionsupporting
confidence: 68%
“…indicators than the C-index, and the NRI indicated that the proposed nomogram reclassified the risk probabilities better than did the AJCC staging system, while the IDI demonstrated the superior ability of the constructed nomogram to distinguish cases compared with the AJCC staging system. Numerous previous studies have found benefits of applying DCA (29)(30)(31)(32)(33), and the results of the current study indicate that the 3-, 5-, and 10-year DCA curves yielded net benefits greater than those of the AJCC staging system, both in the training and validation sets (Figure 4).…”
Section: Discussionsupporting
confidence: 68%
“…The NRI and IDI are more sensitive indicators than the C-index, and the NRI indicated that the proposed model reclassified the risk probabilities better than did the AJCC staging system, while the IDI demonstrated the superior ability of the constructed nomogram to distinguish cases compared with the AJCC staging system. Numerous previous studies have found benefits of applying DCA (29)(30)(31)(32)(33), and the results of the current study showed that the 3-, 5-, and 10year DCA curves displayed net benefits larger than those of the AJCC staging system, both in the training set and validation set (Figure 4).…”
Section: Discussionsupporting
confidence: 63%
“…Up to now, the American Joint Committee on Cancer (AJCC) staging system has always been broadly adopted for cancer management, including BC . However, the current TNM Classification method cannot perfectly provide accurate information to predict patients’ prognosis . Then some patients with BC received unnecessary or excessive medication, while others may be faced with recurrence or metastasis due to lack of appropriate treatment .…”
Section: Introductionmentioning
confidence: 99%